The great power (mis)management the Russian-Georgian war and its implications for global political order - Astrov, Alexander (Ashgate Pub., 2011)
Drawing on the empirical case of the Russian-Georgian war of 2008, this book explores the theoretical underpinnings of the idea of 'great power management' first articulated within the English School of International Relations.